Fish Terminal Design To Reduce Fishermen Operation Costs In Banda Island - Riyadh, Muhammad (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2022)
One of the islands in the Maluku province is a cluster of the Banda Islands. The Banda sea is known as the waters are very rich in various kinds of fish. The center for Economic and Development-LIPI (1999) have calculated the average time fishermen go out to sea in a year as many as 200 days, that entire day, which allowed her to sea. Therefore, at the time of going to sea fishermen use the time optimally to work throughout the day so that it will drain the operational cost and energy fishermen to return to the coastal areas bring their catch to that required terminal of the fish. Teriminal fish serves as a place of temporary suspension to raise and lower the tangakapan fishermen so that it can maintain the quality of the catches of fishermen to the place of destination. The purpose of this study is to design the terminal of fish to help fishermen. Carried out technical calculations such as the determination of the payload, the volume of cargo space, electricity needs, trim, stability and freeboard. As for the size of the main result is Lbp = 81,19 m, B = 15,00 m, H = 7,00 m, and T = 5,50 m and the cost of the construction of the terminal fish Rp 85,053,530,160.11